2004
DOI: 10.2337/diacare.27.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Leucine 7 to Proline 7 Polymorphism in the Preproneuropeptide Y Is Associated With Proteinuria, Coronary Heart Disease, and Glycemic Control in Type 1 Diabetic Patients

Abstract: OBJECTIVE—Neuropeptide Y is a potent vasoconstrictor thought to enhance the development of atherosclerosis. The leucine 7 to proline 7 (Leu7Pro) polymorphism, located in the signal peptide part of the human preproneuropeptide Y, has been associated with serum lipid levels, intima-media thickness of the common carotid arteries, and diabetic retinopathy in type 2 diabetic patients. Therefore, we investigated the impact of the Leu7Pro polymorphism on diabetic nephropathy, cardiovascular risk factors, and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
(25 reference statements)
3
32
2
Order By: Relevance
“…Since then, this polymorphism has been linked to a number of disease conditions, hypertension (Karvonen et al, 2001;Pettersson-Fernholm et al, 2004), increased BMI (Ding et al, 2005;van Rossum et al, 2006), low-density lipoprotein cholesterol (Karvonen et al, 1998;Salminen et al, 2008), serum triglycerides Pihlajamaki et al, 2003), carotid atherosclerosis (Karvonen et al, 2001) type-I diabetes (Ma et al, 2007) and type-II diabetes (Niskanen et al, 2000;Ukkola and Kesaniemi, 2007). As NPY is a plausible candidate for obesity, we conducted a populationbased case-control study to investigate the association between NPY gene single-nucleotide polymorphisms (SNPs) and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this polymorphism has been linked to a number of disease conditions, hypertension (Karvonen et al, 2001;Pettersson-Fernholm et al, 2004), increased BMI (Ding et al, 2005;van Rossum et al, 2006), low-density lipoprotein cholesterol (Karvonen et al, 1998;Salminen et al, 2008), serum triglycerides Pihlajamaki et al, 2003), carotid atherosclerosis (Karvonen et al, 2001) type-I diabetes (Ma et al, 2007) and type-II diabetes (Niskanen et al, 2000;Ukkola and Kesaniemi, 2007). As NPY is a plausible candidate for obesity, we conducted a populationbased case-control study to investigate the association between NPY gene single-nucleotide polymorphisms (SNPs) and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this work provides the first genetic evidence that NPY may be linked to altered cholesterol metabolism and that the polymorphism producing Pro (7) in the NPY signalling peptide may be one of the strongest genetic factors influencing serum cholesterol and LDL levels in obese subjects [16]. Subsequently, the Leu (7)-to-Pro(7) polymorphism has been linked to both type 1 [17] and type 2 diabetes [18,19], atherosclerosis [20] and coronary heart disease [21]. These studies suggest that the NPY T1128C polymorphism may be a strong independent risk factor for various cardiovascular diseases.…”
mentioning
confidence: 76%
“…For example, it is unknown whether this T1128C polymorphism translates into higher or lower levels of active polypeptide NPY because serum or tissue NPY levels were either not measured or vary to a great extent between studies. Pettersson-Fernholm et al [17] found no differences in plasma NPY levels between type 1 diabetic patients with the T1128C allele and those with the wild-type genotype. By contrast, Kallio et al [26] reported significantly lower plasma NPY levels in subjects with the T1128C allele in healthy subjects.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…15 In type 1 diabetes and hypertension patients, the Leu7Pro polymorphism has been associated with cardiovascular events. 16,17 NPY has many immunomodulatory functions: it regulates adhesion and cytokine secretion of T cells, 18,19 stimulates chemotaxis of monocytes 20 and modulates the functions of macrophages. 21 However, the precise role of NPY in the inflammatory cascade in atherosclerosis is not known.…”
Section: Introductionmentioning
confidence: 99%